Leisure and Festive Activities in Russian Army on Frontlines of World War I - V. V. Kanischev; A. N. Pluzhnikov (Научный диалог)
The need to restore lost data on the last major war of the Russian Empire implies a comprehensive coverage of events during those years, including their non-combat component. Based on the study of the “Journals of Military Actions” of combat units, which reflect little-researched stories of non-combat realities of front-line life, the authors offer a new perspective on the military everyday life of the Russian Imperial Army. The article focuses on the “pleasant” and unexpected nuances of the daily lives of soldiers and officers during the difficult years of war. Researchers have turned to such facts of military reality during the specified period as the organization of the award procedure for the command staff and lower ranks, the organization of prayers as integral components of festive events, the conduct of state (imperial) and religious holidays, as well as recreational activities. This work provides an opportunity to obtain an objective understanding of the multifaceted life and everyday life of people in wartime conditions: when circumstances allowed, performances, games, and sports events were organized and held. Without theoretical knowledge in the field of psychology and stress management techniques, the command of the Russian army organized and encouraged activities aimed at alleviating the negative consequences of combat stress.